Translating for Palestine as Self-development: A Translational Perspective on Human Rights and International Development - Jarrar, Rania (Université d'Ottawa | University of Ottawa, 2025)
This thesis examines the translational practices of Local Non-Governmental Organizations (LNGOs) in Palestine and their role in implementing human rights development projects. By conducting semi-structured interviews with representatives from various LNGOs and engaging in an interdisciplinary dialogue between Translation Studies and Development Studies, the research analyzes how these organizations translate and adapt international development concepts to align with local needs and values. This study critiques the conventional perception of translation as a solely linguistic transfer, which often presumes the universality of human rights concepts and overlooks the complexities of cultural and contextual differences. It argues for an expanded definition of translation that encompasses deeper engagement, negotiation, and reciprocity in intercultural exchanges. This research positions translation as a critical epistemic paradigm for understanding and managing the flow of knowledge, values, and terms of references between different contexts, particularly in asymmetrical power dynamics characteristic of international development. By reconceptualizing translation as both an archetype or a perspective and an analytical tool, this study explores how LNGOs navigate tensions between donor expectations and local realities, often reframing human rights principles to resonate more effectively with the Palestinian context. This process extends beyond linguistic conversion to include broader discursive and strategic engagements, highlighting the agency of LNGOs in shaping development discourse. The findings demonstrate that LNGOs’ translational practices contribute to a more nuanced understanding of human rights and development, emphasizing the potential for translation as a broader concept to facilitate self-development and empowerment. This thesis explores an interdisciplinary approach that builds on the common assumptions and paradigms underlying both TS and DS to foster a participatory, context-sensitive development model. By centering local voices and perspectives, this model aims to support Palestinians' self-determination and enhance the effectiveness of human rights initiatives.
Keywords: Translation Studies; Development Studies; International Development; Human Rights; Palestine; West-Bank; Gaza; Translational perspective; Translation as an analytical tool; Translation as an archetype